El Salvador : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1994)
This paper describes economic developments in El Salvador during the 1990s. Since 1990, the government has implemented a major economic reform program, including through a greater reliance on market forces. Although risks remain, financial imbalances have been reduced, economic growth has resumed, and inflation has declined. The government also is modernizing the structure of the public sector, including a reform of public expenditure management. The restructuring of the public finances aims to increase public savings, reorient public expenditure toward increased peace-related expenditure, and increase efficiency in delivering services.